Information Nudges and Tax Service Quality Moderate The Effect of Tax Digitalization and Tax Knowledge on Taxpayer Compliance in Lampung Province - Rizky Oktaviana; Susi Sarumpaet; Ninuk Dewi Kesumaningrum (PT. Altaf Publishing Corp, 2025)
This research is motivated by low tax compliance despite various reforms, including the use of technology and behavioral approaches. The study used a quantitative approach with a survey method in the form of a questionnaire for individual taxpayers who are in business or freelance, analyzed using SEM-PLS. The results show that tax digitalization, tax knowledge, and information nudges have a positive effect on taxpayer compliance. However, information nudges cannot moderate the effect of digitalization or knowledge on compliance, while the quality of tax services proved to be a significant moderator, strengthening the influence of digitalization and tax knowledge on compliance. However, the quality of tax services did not directly affect taxpayer compliance. This finding confirms that technology, knowledge, and public service strategies complement each other in encouraging taxpayer compliance. This study provides practical recommendations for the Directorate General of Taxes (DGT) to continue improving user-friendly digital services and integrating nudging techniques into tax communication strategies because their presence continues to directly show a positive effect on compliance.